BENTHIC DIVERSITY OF RIVER GOMTI IN RELATION TO THE PREVAILING ENVIRONMENTAL CONDITIONS IN LUCKNOW - Varshney, P. K.; Agrahari, R. K.; Singh, S. K.; Jain, A. K. (Journal of Indian Fisheries Association, 2006)
To evaluate the benthic diversity of River Gomti in relation to the prevailing environmental conditions, four stations, viz., Maa Chandrika Devi, Daliganj, Ambedkar Park and Aquaduct, were identified from upstream to downstream along the course of the river in Lucknow. Dissolved oxygen was low on many occasions at an the stations except Maa Chandrika Devi and chemical oxygen demand values were high. There was a gradual increase in mean nitrite and phosphate values from up to down. stream. Benthic fauna was dominated by oligochaetes and chironomus larvae. Other groups reported were leeches, nematodes, sponges, crustaceans, pelycypodes, gastropodes and fish fry. Population density was exceptionally high at Daligan.j (20,135 m-1 ) followed by Ambedkar Park (5,199 m-1 ) and Aquaduct (3,287 m-), and low at Maa Chandrika Devi (264 m-1). Oligochaete genera common. at aU the four stations were Lumbricillus, Limnodrillus, Branch iura, Clwetogw·;ter, Nais and Tubifex. Odonates were reported only from Maa Chandrika Devi while sponges were encountered at Daliganj and Aquaduct. On some occasions, fish fry were also found at Ambedkar Park and Aquaduct. Seasonally, maxima for population density were observed during pre-monsoon and minima during monsoon. The organic poHution indicator benthic species reported were tubificids, chironomids, culicoid larvae, Lamellidens sp., Corbicula sp., Lymnaea sp. and leech. Branchiurans, Tub fex sp. and Chirmwmus larvae were reported at aU the stations. Filthy condition with foul smell throughout the length of the river coupled with poor water quality and appearance of indicator organisms at aU the stations indicate that the river is under severe pollution stress due to anthropogenic discharges and it has reached an alarming stage. Keywords: River Gomti, pollution, indicator species